(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the vocabulary of the Ukrainian language of the late XIX – early XX centuries in the serial edition “The Epistolary Heritage of Academician D. Yavornytsky”, particularly we examine a combination of words and a set of their meanings, which are enshrined in words in the process of centuries-old nation-wide use of language, reproduced in the letters to D. Yavornytsky and his correspondents. We analyze the use of terminological vocabulary; single out words synonyms, combining them into synonymous rows; give a description of the original words and words borrowed from other languages. We characterize the use of emotionally-colored vocabulary in the epistolary framework (initial formulas-appeal and final-farewell) depending on the situation and mood of the author at the time of writing the letter, the relationship with the addressee, the purpose of the message (“Dorohyy ta lyubyy sertsyu moyemu Dmytro Ivanovychu!”, “Dorohyy miy Baydo!”, “Lyubyy miy bratiku Dmytre!”, “Shanovnyy Dobrodiyu!”, “Vysokopovazhnyy pane profesore!”, “Batʹku otamane koshovyy!”, “Vysokopovazhanyy Dobrodiyu”, “Lyubyy miy Kesaryu!”, “Druzhe miy lyubyy, druzhe miy virnyy!”, “Velʹmy shanovnyy Boryse Dmytrovychu!”, “Dorohyy kume Ivane Mykhaylovychu!”). Estimated value of the epistolary of D. Yavornytsky and his correspondents appear in the names-characteristics of people – “tyamushchykh filolohiv”, “merzennyy cholovik”, “orle syzyy”, “dorohyy kozache”, “prekhoroshyy pratsʹovnyk”; in characterization of the environment – “po shlyakham ta po beskeddyam”, “z berehiv Dnipra do tykhoyi Samari”; buildings – “moya khatyna”, “u khutoretsʹ”; emotional qualification of human actions – “poviyavsya do Yessentukiv”, “siday mershchiy zakalamarʹ”; process of speaking – “bovknu tobi”, “havkny, abo vyshchyrʹ zuby”, “rubayete po-poltavsʹkomu”, “yazyk u dida rozkishnyy”.